DYNAMIC GOVERNANCE DALAM SISTEM INFORMASI PELAYANAN PERIZINAN TERPADU (SIPPADU) OLEH DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KABUPATEN SIDOARJO - Desvananda Putra Purwanto, Auditya; Hardjati, Susi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The era of disruption and the policy of centralizing licensing through the Online Single Submission Risk-Based Approach (OSS-RBA) pose challenges to innovation in public services at the local level. This study aims to analyze the application of Dynamic Governance capabilities in the implementation of the Integrated Licensing Service Information System (SIPPADU) application at the Investment and One-Stop Integrated Service Agency (DPMPTSP) of Sidoarjo Regency. The method used is qualitative with a descriptive approach. Data collection was conducted through in-depth interviews, observations, and document analysis using purposive sampling to select informants. Data analysis employed the Miles and Huberman interactive model, while the analytical framework utilized the Dynamic Governance theory by (Neo & Chen, 2007), which encompasses the aspects of “thinking ahead,” “thinking again,” and “thinking across.” The research results indicate that the Sidoarjo Regency DPMPTSP has comprehensively implemented all three of these capabilities. The “thinking ahead” aspect was implemented through a strategy to reposition SIPPADU as a complementary application to handle permits not covered by the OSS. The “thinking again” aspect was realized by redesigning SIPPADU into a “Next Generation” version based on performance evaluations and public feedback. Meanwhile, the “thinking across” aspect is achieved by adopting innovative practices from other agencies and combining them with local technological assets. This synergy of capabilities has proven effective in maintaining SIPPADU’s role as an adaptive, complementary system for ensuring the quality of public services in the region.